O conceito de infinito em Spinoza - Bezerra, Marcio Roberto Soares (2014)
This essay aims to discourse on the concept of infinite in Baruch Spinoza, taking as main theoretical reference two of his works, the Metaphysical Thoughts and The Letter 12. The objective is to show that the concept of infinite represents a key idea to Spinoza s system, where all his theses concerning immanent causality and psychophysical parallelism are based on. The research begins with a historical approach about the matter of infinite, discussed by a tradition of thinkers who preceded Spinoza, since the Greeks until Descartes in modernity. In a second moment, the analysis turns to the matter of infinite understood by Spinoza who, as he defends the idea of current infinite, ends up retaking the theory of Anaxagoras, Nicolau of Cusa and Giordano Bruno, where, according to them, God is not separated of his creatures, but keeps a relation of immanency with them. In this case, according to Spinoza, to affirm that God is infinite means saying that He comprehends all things and nothing can exist separated from Him, and moreover, being substance, God cannot be separate of his conditions (modes), what is explained by the immanency of his causality, in what cause (God) and effect (modes) occur simultaneously. The habit of separate the substance from his conditions comes from the misunderstanding between the way how the mind understands the substance through the beings of Reason (time, measure, number) and the essence of the own substance. Through the beings of Reason, the substance is composed of parts and, therefore, it is divisible; however, considering its essential aspect, it is indivisible. This explains the thesis of parallelism as well since mind and body, due to inseparability of conditions, cannot be considered independent substances, but expressions of a single and same substance, either conceived by the attribute of thinking, or conceived by the attribute of extension. According to Spinoza, the dualism proposed by his main interlocutor, Descartes, precisely appeared due to the fact of his misunderstanding concerning the real aspect of substance (indivisible attributes) with his modal aspect (divisible modes).